Construction of an Aspergillus nidulans cDNA library suitable for use in a yeast two hybrid screen - Wan-Sheng Lo; Diana C. Bartelt (Fungal Genetics Reports, 1996)
We have constructed a plasmid library containing cDNAs from Aspergillus nidulans fused to the activation domain of yeast GAL4. When transformed into S. cerevisiae the Hf7c reporter host strain containing a plasmid with a "bait" DNA fused to the GAL4 DNA binding domain, this library can be used to screen for interactions between the gene products encoded by the cDNA and the target protein encoded by the "bait" DNA.